2011
DOI: 10.1093/toxsci/kfr180
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Activation Is Required in Reactive Oxygen Species Generation and Cell Transformation Induced by Hexavalent Chromium

Abstract: Hexavalent chromium [Cr(VI)] is a well-known human carcinogen associated with the incidence of lung cancer. Although overproduction of reactive oxygen species (ROS) has been suggested to play a major role in its carcinogenicity, the mechanisms of Cr(VI)-induced ROS production remain unclear. In this study, we investigated the role of NADPH oxidase (NOX), one of the major sources of cellular ROS, in Cr(VI)-induced oxidative stress and carcinogenesis. We found that short-term exposure to Cr(VI) (2μM) resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 37 publications
6
100
1
Order By: Relevance
“…Phosphorylation of EGFR at tyrosine1068 was much higher at the exposure duration of 4 months and 6 months than that of 2 months and 3 months. At this stage of chronic Cr(VI) exposure (6 months), the cells were malignant transformed as examined by anchorage-independent cell growth (soft agar) assay (data not shown), similar to those observation in our previous study (17). Phosphorylation of EGFR at Tyr-1068 was highest in both two clones of transformed cells isolated from the cells exposed to Cr(VI) for 6 months compared with various durations of Cr(VI) exposure (Fig.…”
Section: Activations Of Egfr In Cr(vi)-transformed Cells and Cr(vi)-supporting
confidence: 89%
See 3 more Smart Citations
“…Phosphorylation of EGFR at tyrosine1068 was much higher at the exposure duration of 4 months and 6 months than that of 2 months and 3 months. At this stage of chronic Cr(VI) exposure (6 months), the cells were malignant transformed as examined by anchorage-independent cell growth (soft agar) assay (data not shown), similar to those observation in our previous study (17). Phosphorylation of EGFR at Tyr-1068 was highest in both two clones of transformed cells isolated from the cells exposed to Cr(VI) for 6 months compared with various durations of Cr(VI) exposure (Fig.…”
Section: Activations Of Egfr In Cr(vi)-transformed Cells and Cr(vi)-supporting
confidence: 89%
“…It has been reported that EGFR mRNA level was increased in BEAS-2B cells exposed to 1 M of Cr(VI) up to 8 culture passages (14). Our previous study has demonstrated that chronic exposure of BEAS-2B cells to Cr(VI) was able to induce malignant cell transformation (17). The present study has found that EGFR was constitutively activated in Cr(VI)-transformed BEAS-2B cells.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Activity of NADPH oxidase was measured according to Wang et al [30]. The ratio of lucigenin oxidation was normalized to protein content (quantified with a Pierce BCA protein assay kit).…”
Section: Nadph Oxidase Activitymentioning
confidence: 99%